Implementación de un sistema de gas natural por ducto en un establecimiento de venta de GNV con unidad de trasvase - Delgado Leon, Emilio Mario (2022)
The present work has as objective, the proposal for the implementation of a natural gas (NG) system by pipeline, in an existing natural gas sales establishment, replacing the current technology of distribution by land transport of compressed natural gas. (CNG.), this in order to generate economic benefits in one of the organization's NG sales establishments. In addition, engineering tools were applied for the diagnosis of the problems of the current NG system, also for the development of proposals such as the PHVA cycle (Plan, Do, Verify, Act), for the planning of the implementation project of the new technology, and the TPM (Total Productive Maintenance) for the development of strategies that allow the improvement in the integral productivity of the operations area, of the technical and administrative personnel, of the application of maintenance procedures and improvement of the performance of the compressor equipment. As a result of the implementation, an OEE indicator of 85,7% of the NG compressor equipment was obtained at the end of the second half of 2020, representing an increase of 17% compared to the 2019 period. In the first half of 2021, losses of inventory less than 1% with respect to the flow of NG entered. The period was completed with an increase in sales of 35,7%, with a daily flow of 5 499,18 ¿3/day, using the new pipeline distribution system at Servicentro Chimbote.